Design and Simulation of Mill Turn Vise - Nijam @ Nizam, Mohamad Nazrin; Shaari, Norlida; Ibrahim, Badaruddin (Research and Innovation in Technical and Vocational Education and Training, 2021)
The design and development of a product are moving along with the rapid development of the machining industry. The development of this product plays an important role in providing exposure to researchers in the field of design and the use of jigs and fixtures. The purpose of this study is to design and perform FEA (Finite Element Analysis) to 3D model of Mill Turn Vise. This product focuses on the machining industry in particular and students who are in the field of machining in general. The design of this study is using the ADDIE model which consists of five phases namely analysis, design, development, implementation and evaluation. A form of data collection was also developed together to facilitate the technical data collection process. This product is expertly certified through instrument of design selection matrix and technical data generated through FEA analysis simulations using Solidworks software. Based on the data collected through two types of simulations (modal and structural) of three materials (aluminum, carbon steel and cast iron) and data collection forms, this product is practically safe to use in the precision industry as a preliminary exposure to the turning process that can be done on a CNC Milling Machine.